2019
DOI: 10.3390/en12091763
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research of High-Temperature and High-Pressure Water Jet Characteristics in ICRC Engine Relevant Conditions

Abstract: The internal combustion Rankine cycle (ICRC) concept provides a potential solution for future high thermal efficiency and low emission powertrains, and direct water injection (DWI) proved to be the key parameter for ICRC optimization. This paper was dedicated to investigating the fundamental mechanisms of water spray characteristics under different water injection control parameters. In order to do so, an experimental test system was carefully designed and built based on the Bosch and Schlieren methods: the Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…When the steam is introduced into a cylinder during the compression stroke, the power output increases by 5.9% to 7.8% at full load, while the injection timing moves from −120 • to −30 • CA ATDC [20]. The steam assist technology was also applied to the control and optimization of the elevated combustion temperature in the engine with an oxy-fuel combustion mode [21][22][23][24]. Wu et al [25][26][27][28][29] conducted theoretical and experimental studies on the internal combustion Rankine cycle to achieve high thermal efficiency and a low emission powertrain.…”
Section: Introductionmentioning
confidence: 99%
“…When the steam is introduced into a cylinder during the compression stroke, the power output increases by 5.9% to 7.8% at full load, while the injection timing moves from −120 • to −30 • CA ATDC [20]. The steam assist technology was also applied to the control and optimization of the elevated combustion temperature in the engine with an oxy-fuel combustion mode [21][22][23][24]. Wu et al [25][26][27][28][29] conducted theoretical and experimental studies on the internal combustion Rankine cycle to achieve high thermal efficiency and a low emission powertrain.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has been studying the ICRC for many years. Studies on ICRC engines with different fuels (gasoline, diesel, and propane), ignition modes (spark ignition and compression ignition), and water injection strategies (PWI and DWI) have been carried out successively. The previous engine bench tests showed that water injection technology could significantly improve engine performance and emission characteristics under full load conditions while effectively controlling in-cylinder temperature to suppress knocking. We also found that excessive water injection could prolong combustion duration and worse combustion.…”
Section: Introductionmentioning
confidence: 99%